2019
DOI: 10.1007/s00417-019-04328-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home reading training on reading and quality of life in AMD—a randomized and controlled study

Abstract: Background Age-related macular degeneration (AMD) causes reading impairment, reduced quality of life (QoL), and secondary depression. We have shown that support with magnifying aids improved reading speed (RS), emotional and cognitive status, and QoL. The present study investigates whether additional reading training (RT) (after adapting to appropriate visual aids) can further improve vision rehabilitation. Methods Patients with dry AMD were randomly assigned to 2 groups. The primary RT group (P-RTG, n = 25) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 55 publications
7
17
0
1
Order By: Relevance
“…In addition, our results indicated a potential bene cial effect of CLAIs on reduced mortality risk among participants who were diagnosed with cardiovascular or metabolic disease (HR = 0.67, P = 0.025 in univariate analysis, HR = 0.69, P = 0.054 in multivariate analysis, Figure 3). Accumulating evidence has indicated that leisure activity, including watching TV 20 , internet use 21 and reading 22,23 , can make a signi cant contribution to overall life satisfaction and psychological well-being 24,25 , which is subsequently associated with a lower risk of cardiovascular disease 61,62 . Thus, a potential pathway by which cognitive leisure activity in uences all-cause mortality may be through reducing the risk of cardiovascular disease or reducing the effect of cardiovascular disease on mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results indicated a potential bene cial effect of CLAIs on reduced mortality risk among participants who were diagnosed with cardiovascular or metabolic disease (HR = 0.67, P = 0.025 in univariate analysis, HR = 0.69, P = 0.054 in multivariate analysis, Figure 3). Accumulating evidence has indicated that leisure activity, including watching TV 20 , internet use 21 and reading 22,23 , can make a signi cant contribution to overall life satisfaction and psychological well-being 24,25 , which is subsequently associated with a lower risk of cardiovascular disease 61,62 . Thus, a potential pathway by which cognitive leisure activity in uences all-cause mortality may be through reducing the risk of cardiovascular disease or reducing the effect of cardiovascular disease on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It is projected that, by 2050, 1.6 million or 43% of older adult deaths will be due to dementia and Alzheimer's disease 19 . In addition, accumulating evidence has indicated that leisure activity, including watching TV 20 , internet use 21 and reading 22,23 , can make a signi cant contribution to overall life satisfaction [24][25][26] , which has been identi ed as an important risk factor for mortality in older people [27][28][29] . Recently, a prospective cohort study indicated that playing cards or mahjong and reading were association with lower all-cause mortality in the Chinese oldest-old population 30 .…”
Section: Introductionmentioning
confidence: 99%
“…3). Accumulating evidence have indicated that leisure activity, including watching TV 20 , internet use 21 and reading 22,23 , can make a signi cant contribution to overall life satisfaction and psychological well-being 24,25 , which in turn is associated with lower risk of cardiovascular disease 58,59 . Thus, a potential pathway by which mental activity in uence all-cause mortality may be through reducing the risk of cardiovascular disease or reducing the effect of cardiovascular disease on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to correlate macular subfields with the near-distance activities sub-score of the VFQ because the inability of patients with AMD to maintain steady fixation is strongly associated with slower reading [26]. This particular aspect of visual function can affect quality of life in patients with AMD [27].…”
Section: Discussionmentioning
confidence: 99%